Managing Online Business Through E-Commerce: Empirical study in the store MR. Keramik, Pasuruan - Sukma A.D., Ayu; Della A., Ratna; Sudarmiatin; Wijijayanti, Trisetia (International Humanity Advance, Business & Sciences, 2025)
This research examines online business management strategies through e-commerce platforms at MR. Keramik Store in Pasuruan, East Java. The study employs a qualitative case study methodology with data collection through in-depth interviews, direct observation, and documentation analysis conducted in October 2024. Findings reveal that MR. Keramik successfully implements a multi-platform strategy utilizing Shopee as the primary marketplace (contributing 50-55% of online sales), Instagram for visual merchandising and community building (8,456 followers), and Facebook for B2B segment targeting (2,341 followers). The differentiation strategy emphasizes personalized consultation services rather than competing solely on price. Key challenges include limited human resources, digital competency gaps, intense price competition, and logistical complexities for fragile and heavy products. E-commerce adoption has significantly transformed business performance, increasing monthly sales from IDR 50-60 million (pre-e-commerce) to IDR 160-180 million, with online channels contributing 60-65%. Geographic reach expanded from a 30-40 km radius to national coverage, with active customers growing from 300-400 to 2,800-3,000. This study contributes to the literature on SME digital transformation in developing countries, particularly in the under-researched building materials retail sector.